Recurrent Co-Option and Recombination of Cytokine and Three Finger Proteins in Multiple Reproductive Tissues Throughout Salamander Evolution - Wilburn, Damien B.; Kunkel, Christy L.; Feldhoff, Richard C.; Feldhoff, Pamela W.; Searle, Brian C. (Frontiers in Cell and Developmental Biology, 2022)
Reproductive proteins evolve at unparalleled rates, resulting in tremendous diversity of both molecular composition and biochemical function between gametes of different taxonomic clades. To date, the proteomic composition of amphibian gametes is largely a molecular mystery, particularly for Urodeles (salamanders and newts) for which few genomic-scale resources exist. In this study, we provide the first detailed molecular characterization of gametes from two salamander species (Plethodon shermani and Desmognathus ocoee) that are models of reproductive behavior. Long-read PacBio transcriptome sequencing of testis and ovary of both species revealed sex-specific expression of many genes common to vertebrate gametes, including a similar expression profile to the egg coat genes of Xenopus oocytes. In contrast to broad conservation of oocyte genes, major testis transcripts included paralogs of salamander-specific courtship pheromones (PRF, PMF, and SPF) that were confirmed as major sperm proteins by mass spectrometry proteomics. Sperm-specific paralogs of PMF and SPF are likely the most abundant secreted proteins in P. shermani and D. ocoee, respectively. In contrast, sperm PRF lacks a signal peptide and may be expressed in cytoplasm. PRF pheromone genes evolved independently multiple times by repeated gene duplication of sperm PRF genes with signal peptides recovered through recombination with PMF genes. Phylogenetic analysis of courtship pheromones and their sperm paralogs support that each protein family evolved for these two reproductive contexts at distinct evolutionary time points between 17 and 360 million years ago. Our combined phylogenetic, transcriptomic and proteomic analyses of plethodontid reproductive tissues support that the recurrent co-option and recombination of TFPs and cytokine-like proteins have been a novel driving force throughout salamander evolution and reproduction.